2016
DOI: 10.3325/cmj.2016.57.558
|View full text |Cite
|
Sign up to set email alerts
|

Tongue somatosensory evoked potentials reflect midbrain involvement in patients with clinically isolated syndrome

Abstract: AimTo test the hypothesis that tSSEP findings reflect clinical and MRI MS lesions, the aim of this study was to investigate tSSEP changes in patients with clinically isolated syndrome (CIS) in relation to clinical and brainstem MRI findings. The second aim was to investigate whether the interpretation of the tSSEP results in the form of the tSSEP score enables better evaluation of the afferent trigeminal pathway involvement than analyzing each tSSEP parameter separately.Methods115 consecutive CIS patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…In our previous work, it has been shown that the VEMP score has the ability to detect brainstem dysfunction in different populations of MS (both CIS and relapsing–remitting MS) and there is a good correlation between VEMPs and clinical dysfunction of the brainstem, the presence of MRI lesions in the brainstem, but also with measures of disability like EDSS and 9HPT . The tSSEP score, on the other hand, reflects MRI changes in the midbrain, further expanding the utility of EPs to detect brainstem damage in MS . The finding of the present study, in which VEMPs and tSSEPs have been combined with other EPs, provides new evidence for the importance of the brainstem in the development of future disability in pwCIS.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In our previous work, it has been shown that the VEMP score has the ability to detect brainstem dysfunction in different populations of MS (both CIS and relapsing–remitting MS) and there is a good correlation between VEMPs and clinical dysfunction of the brainstem, the presence of MRI lesions in the brainstem, but also with measures of disability like EDSS and 9HPT . The tSSEP score, on the other hand, reflects MRI changes in the midbrain, further expanding the utility of EPs to detect brainstem damage in MS . The finding of the present study, in which VEMPs and tSSEPs have been combined with other EPs, provides new evidence for the importance of the brainstem in the development of future disability in pwCIS.…”
Section: Discussionsupporting
confidence: 66%
“…Moreover, the superiority of VEMPs in the evaluation of the brainstem compared to AEPs has been demonstrated previously . Similarly, the tSSEP score was created and its association with MRI‐verified midbrain lesions in a cohort of pwCIS was shown .…”
Section: Introductionmentioning
confidence: 65%
“…Although several lines of evidence suggest that TSSEP are superior to AEP in pwMS, the problem with this EP modality are numerous existing protocols with different modalities, locations and frequencies of stimulation, and different electrode positions to record the response. We have previously shown in a relatively large group of subjects with CIS that one of the TSSEP variants, tSSEP was pathologically altered in 32% of participants (KrbotSkorić et al, 2016). In addition, the absence of response to tSSEP was statistically significantly correlated with MRIproven lesions in the brainstem, more specifically in the pons and the midbrain.…”
Section: Discussionmentioning
confidence: 85%
“…Consecutive persons who presented with an acute or subacute episode of neurological dysfunction due to inflammatory demyelination that lasted more than 24 h and occurred in the absence of fever, infection, or encephalopathy, and with at least one demyelinating lesion larger than 3 mm on brain and/ or spinal cord MRI were enrolled into the study from August 1st 2014 until the 1st of February 2016. Baseline data on initial 121 patients have previously been reported (KrbotSkorić et al, 2016). Exclusion criteria included corticosteroids within 30 days prior to testing, dental braces and any other piercing in the tongue or lips which could not be removed during testing.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation